Exploring the complex interplay of polymyxin resistance mechanisms, lipid A variations, and virulence factors in Escherichia coli and Klebsiella pneumoniae - Ballaben, Anelise Stella [UNESP]; Ferreira, Joseane Cristina; Tonani, Ludmilla; Volpato, Fabiana Caroline Zempulski; Barth, Afonso Luís; de Oliveira Garcia, Doroti; von Zeska Kress, Marcia R.; Doi, Yohei; Ernst, Robert K.; da Costa Darini, Ana Lúcia (Elsevier, 2025)
The global emergence of multidrug-resistant (MDR) and extensively drug-resistant (XDR) Escherichia coli and Klebsiella pneumoniae poses a serious public health concern due to limited therapeutic options. Polymyxins, often considered last-resort antibiotics, are increasingly compromised by resistance mechanisms such as lipid A modifications and plasmid-mediated genes like mcr-1. In this study, we investigated phenotypic and genotypic features of polymyxin-resistant clinical isolates from Brazilian hospitals. Seventeen Gram-negative bacilli (14 E. coli, 3 K. pneumoniae) were analyzed through antimicrobial susceptibility testing, lipid A profiling via mass spectrometry, whole-genome sequencing (WGS), and virulence assessment using the Galleria mellonella infection model. Resistance was associated with structural modifications of lipid A including phosphoethanolamine (PEtN), L-Ara4N, palmitate, and LpxO-mediated hydroxylation, and the presence of major resistance genes such as mcr-1.1, bla NDM-1, and bla CTX-M-15. Genetic context analysis revealed associations with mobile elements like ISEcp1 and ISCR1, as well as integron-associated gene cassettes (e.g., aadA2, dfrA12). MLST showed high clonal diversity among E. coli isolates, including ST10, ST131, ST354, and ST410, and detection of K. pneumoniae ST11 and ST4477, the former being a dominant high-risk clone in Brazil and worldwide. Virulence profiling revealed heterogeneous phenotypes, with some strains classified as hypervirulent. Overall, our findings underscore the complexity of resistance and virulence mechanisms in clinical Enterobacterales and highlight the importance of genomic surveillance to monitor the dissemination of MDR/XDR pathogens.